Incidence of Type 2 diabetes among occupational classes in Sweden: a 35‐year follow‐up cohort study in middle‐aged men. Issue 6 (25th February 2014) - Hedén Stahl, C.; Novak, M.; Hansson, P.‐O.; Lappas, G.; Wilhelmsen, L.; Rosengren, A.
Abstract Aims To assess if low occupational class was an independent predictor of Type 2 diabetes in men in Sweden over a 35‐year follow‐up, after adjustment for both conventional risk factors and psychological stress. Methods A random population‐based sample of 6874 men aged 47–56 years without a history of diabetes was divided into five occupational classes and the men were followed from 1970 to 2008. Diabetes cases were identified through the Swedish inpatient and death registers. Subdistribution hazard ratios (SHRs) and 95% CIs from competing risk regressions, cumulative incidence and conditional probabilities were calculated, after accounting for the risk of death attributed to other causes. Results A total of 907 (13%) men with diabetes were identified over 35 years with a median follow‐up of 27.9 years. The cumulative incidence of diabetes, when taking into account death as a competing event, was 11% in high officials, 12% in intermediate non‐manual employees, 14% in assistant non‐manual employees, 14% in skilled workers, and 16% in unskilled and semi‐skilled workers. Men with unskilled and semi‐skilled manual occupations had a significantly higher risk of diabetes than high officials (reference) after adjustment for age, BMI, hypertension, smoking and physical activity (SHR 1.39, 95% CI 1.08–1.78). Additional adjustment for self‐reported psychological stress did not attenuate the results. Conclusions A low occupational class suggests a greater risk of Type 2 diabetes, independently of conventional risk factors and psychological stress.